The health seeking trajectories of malaysian women and their husbands in delay cases of breast cancer: A qualitative study - Yusoff, Nasir; Mohd Taib, Nur Aishah; Ahmad, Aini (Asian Pacific Organization for Cancer Prevention, 2011)
The aim of this study was to assess why women delay in getting treatment (i.e. surgery) for breast cancer, as well as to explore on what type of issues are involved in such delay cases. Basic interpretative of qualitative methodology was applied to construct the reality of delay phenomena, and its interaction with social worlds. Six themes were identified: new conception of breast cancer treatment, psychological defenses, health support system, symtomatology experience, model and barriers. The delay issue in breast cancer requires attention as a multidimensional problem as this will facilitate more comprehensive and effective intervention to reduce delay.